Proton beam range verification by means of ionoacoustic measurements at clinically relevant doses using a correlation-based evaluation - Schauer, Jannis; Wieser, Hans-Peter; Huang, Yuanhui; Ruser, Heinrich; Lascaud, Julie; Würl, Matthias; Chmyrov, Andriy; Vidal, Marie; Herault, Joel; Ntziachristos, Vasilis; Assmann, Walter; Parodi, Katia; et al. (Frontiers in Oncology, 2022)
Purpose: The Bragg peak located at the end of the ion beam range is one of the main advantages of ion beam therapy compared to X-ray radiotherapy. However, verifying the exact position of the Bragg peak within the patient online is a major challenge. The goal of this work was to achieve submillimeter proton beam range verification for pulsed proton beams of an energy of up to 220MeV using ionoacoustics for a clinically relevant dose deposition of typically 2Gy per fraction by using optimal proton beam characteristics for ionoacoustic signal generation and improved signal detection by correlating the signal with simulated filter templates. Methods: A water tank was irradiated with a preclinical 20MeV proton beam using different pulse durations ranging from 50ns up to 1µs in order to maximise the signal-to-noise ratio of ionoacoustic signals. The ionoacoustic signals were measured using a piezo-electric ultrasound transducer in the MHz frequency range. The signals were filtered using a cross correlation-based signal processing algorithm utilizing simulated templates, which enhances the SNR of the recorded signals. The range of the protons is evaluated by extracting the time of flight of the ionoacoustic signals and compared to simulations from a Monte Carlo dose engine (FLUKA). Results: Optimised SNR of 28 is obtained at a beam current of 4.5µA and a pulse duration of 130ns at a total peak dose deposition of 0.5Gy. Evaluated ranges coincide with Monte Carlo simulations better than 0.1mm at an absolute range of 4.2mm. Higher beam energies require longer proton pulse durations for optimised signal generation. Using the correlation-based post-processing filter a SNR of 17.8 is obtained for 220MeV protons at a total peak dose deposition of 1.3Gy. For this clinically relevant dose deposition and proton beam energy, submillimeter range verification was achieved at an absolute range of 303mm in water. Conclusion: Optimal proton pulse durations ensure an ideal trade-off between maximising the ionoacoustic amplitude and minimising dose deposition. In combination with a correlation-based post-processing evaluation algorithm, a reasonable SNR can be achieved at low dose levels putting clinical applications for online proton or ion beam range verification into reach.